2020
DOI: 10.1111/epi.16548
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of perampanel monotherapy for focal and generalized tonic‐clonic seizures: Experience from a national multicenter registry

Abstract: Objective: To assess the effectiveness and tolerability of perampanel (PER) monotherapy in routine clinical practice for the treatment of focal onset and generalized tonic-clonic seizures (GTCS). Methods: This multicenter, retrospective, observational study was conducted in patients aged ≥12 years treated with PER as primary monotherapy or converted to PER monotherapy by progressive reduction of background antiepileptic drugs. Outcomes included retention, responder, and seizure-free rate after 3, 6, and 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 28 publications
(62 reference statements)
10
40
0
1
Order By: Relevance
“…The median maintenance dose of perampanel used was 4 mg/day (interquartile range: 4-6). 10 At 3, 6, and 12 months since initiation of perampanel treatment, respectively, retention rates were 93.8%, 89.3%, and 80.9%, responder rates were 79.6%, 70.1%, and 52.8%, and seizure freedom rates were 62.7%, 56.1%, and 41.5%. Regardless of whether perampanel monotherapy was given as the primary or secondary treatment, retention rates did not vary (P=0.57).…”
Section: Real-world Data Monotherapymentioning
confidence: 93%
See 3 more Smart Citations
“…The median maintenance dose of perampanel used was 4 mg/day (interquartile range: 4-6). 10 At 3, 6, and 12 months since initiation of perampanel treatment, respectively, retention rates were 93.8%, 89.3%, and 80.9%, responder rates were 79.6%, 70.1%, and 52.8%, and seizure freedom rates were 62.7%, 56.1%, and 41.5%. Regardless of whether perampanel monotherapy was given as the primary or secondary treatment, retention rates did not vary (P=0.57).…”
Section: Real-world Data Monotherapymentioning
confidence: 93%
“…Based on clinical trial data and real-world experience, perampanel is observed to have broad-spectrum efficacy in a range of seizure types when used as both monotherapy and adjunctive therapy. [7][8][9][10][11][12] Clinical studies and real-world evidence have demonstrated the benefits of initiating perampanel at low doses (≤6 mg) [7][8][9][10][11][12] and utilizing a slow titration strategy (increasing dose by 2 mg at ≥2-week intervals). 7,[14][15][16] Initiating perampanel at an early stage (as initial monotherapy or early adjunctive therapy) has also been shown to be associated with better patient outcomes; these data are described below.…”
Section: Key Clinical and Real-world Evidence On Perampanelmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with reports of PER used as monotherapy. An examination of data from a national multicenter registry showed that when PER was administered as monotherapy in patients with focal or generalized tonic-clonic seizures, it was effective at a low dose in most patients (Toledano Delgado et al, 2020). When used as monotherapy, the effectiveness of PER was also reported for the patients with genetic generalized epilepsy (Alsaadi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%